The seduction of modern Spain the female body and the Francoist body politic - Morcillo, Aurora G. 1962-2020 (Bucknell University Press, 2010)
This book examines how sexual politics, specifically those surrounding the modernization of a consumer economy, are key to understanding the transformation of Spain from isolated dictatorship to modern state. It focuses on issues concerning modernity and the commodification of the female body under the dictatorship of Francisco Franco in the 1950s and 1960s. These two decades are critical to understanding this transformation because they coincide with the opening of markets, the freer movement of people in and out of the country through tourism and emigration, and the embracing of the "American way of life" popularized in Hollywood movies. From a gender perspective this "in between moment" in Homi Bhabha's terms, from autarchy to consumerism favored the transition from the virginal female model, prescribed by the regime, (what the author calls "True Catholic Womanhood") to a seductive modern woman that the media sold to Spanish women
Keywords: Geschichte 1950-1975; Politik; Körper; Frau; Spanien; Women / Spain / Social conditions / 20th century; Sex role / Spain / History / 20th century; Body image / Spain / History / 20th century; Francoism; Spain / Politics and government / 1939-1975; Femmes / Espagne / Conditions sociales / 20e siècle; Rôle selon le sexe / Espagne / Histoire / 20e siècle; Image du corps / Espagne / Histoire / 20e siècle; Franquisme; Espagne / Politique et gouvernement / 1939-1975; Body image; Politics and government; Sex role; Women / Social conditions; Spain / https://id.oclc.org/worldcat/entity/E39PBJqFTrvj6Mhw6JfTGmqJDq; 1900-1999; History